(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In the course of research on the territory of the PreUstyurt autonomous plague focus in 2017-2021 a decrease of the number of great gerbils was revealed. The main reason is the influence of unfavorable external factors, including weather conditions (drought), which led to a decrease in the density of rodent settlements and, as a result, to a change in the structure of populations.